Penerapan Metode Activity Based Costing Dalam Menentukan Besarnya Tarif Jasa Rawat Inap Pada Rumah Sakit Umum Daerah Kota Padangsidimpuan - Kamilah; Kusmilawaty; Putri Rahmaini Suheri (PT. Hasba Edukasi Mandiri, 2025)
Hospitals are non-profit organizations whose main task is to provide medical services, care, and health services. In providing health services, hospitals generate revenue from the services and facilities offered to patients, one of which is inpatient services, where the revenue from this service is obtained from the rates that must be paid by inpatient service users. Determining the inpatient service rates is a very important decision because it will affect the hospital's profitability. This research was conducted at the Regional General Hospital (RSUD) of Padangsidimpuan City. The objective of this study is to determine the inpatient service rate when applied using the activity-based costing method at RSUD Padangsidimpuan City. The method used is descriptive analysis. The results of the inpatient service rate calculation using the activity-based costing method show a lower rate compared to the rate previously set by RSUD Padangsidimpuan City.